Zarządzanie terminologią w ramach kierunku studiów „Lingwistyka w komunikacji specjalistycznej” - Plęs, Łukasz M. (2022)
The present paper is an attempt to discuss the issue of terminology management as a part of the translator or LSP training process as well as the methods of its implementing within the degree course “Linguistics in Specialised Communication”. The course of terminology management discussed in the paper consists of a theoretical and a practical module. The second one includes three steps: terminology work sensu stricto, terminology management and integrating of termbases being prepared or made available in the process of translation with the aid of the TMS and CAT tools. The practical work was based on small and medium-sized terminology projects carried out by university students.
Keywords: terminology; terminology work; terminology management; terminology project; language for specific purposes; computer-assisted translation